Honour, mana, and agency in Polynesian-European conflict - Wilkes, Annette, author.
1 online resource (1 volume)
Keywords: Focusing on the era of "first encounters" in Polynesia, this book provides a fresh look at some of the early contacts between indigenous people and the captains and crew of European ships. The case studies chosen enable comparison of New Zealand Maaori-European transactions with similar Pacific ones. The book examines the conflict situations that arose and the reasons for physical violence, highlighting the roles of honour, mana, and agency. Drawing on a range of archival materials, sailor and missionary journals, as well as indigenous narratives, Wilkes applies an analytical method typically used for examining much more recent conflict. She compares different ways of "seeing" and "knowing" the world and reflects on the reasons for poor decision-making amongst all the social actors involved. The evidence presented in the book strongly suggests that preventing violence - promoting and negotiating peace - happens most effectively when mana and honour are acknowledged between parties.